2022
DOI: 10.1021/acs.jafc.2c03133
|View full text |Cite
|
Sign up to set email alerts
|

Improving Insecticidal Activity of Chlorantraniliprole by Replacing the Chloropyridinyl Moiety with a Substituted Cyanophenyl Group

Abstract: Insect ryanodine receptors (RyRs) are molecular targets of the anthranilic diamide insecticides. In the present study, a new series of anthranilic diamides containing a cyanophenyl pyrazole moiety were rationally designed by active-fragment assembly and computer-aided design using the 3D structure of Plutella xylostella RyRs as a receptor and chlorantraniliprole as a ligand. Most of the titled compounds showed good toxicity against Mythimna separate, P. xylostella, and Spodoptera frugiperda. Compounds CN06, CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 49 publications
(75 reference statements)
0
33
0
Order By: Relevance
“…Calcium imaging-based studies were conducted as described in the reported literature. 39,41 Isolation of M. separata Neurons. M. separata were initially obtained from shallot fields in Tianjin, China, and reared indoors in climatic chambers on an agar-based semisynthetic diet at 27 ± 1 °C, 75 ± 5% relative humidity, and 16:8 h light:dark (LD) photocycle.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Calcium imaging-based studies were conducted as described in the reported literature. 39,41 Isolation of M. separata Neurons. M. separata were initially obtained from shallot fields in Tianjin, China, and reared indoors in climatic chambers on an agar-based semisynthetic diet at 27 ± 1 °C, 75 ± 5% relative humidity, and 16:8 h light:dark (LD) photocycle.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The reported mutations such as G4946E and I4790M of P. xylostella RyRs, G4900E and I4743M of Spodoptera exigua RyRs, and G4910E and I4758 M of Chilo suppressalis RyRs were used for locating the homology amino acid mutant sequences of S. frugiperda RyRs, corresponding to G4891E and I4734M of S. frugiperda RyRs, respectively. Therefore, software UCSF chimera 1.16 was used to construct mutant models of S. frugiperda RyRs - E4891 by mutating GLY to GLU, S. frugiperda RyRs - M4734 by mutating ILE to MET . The homology models were refined by YASARA and evaluated by Ramachandran plots (in Supporting Information Figures A and C–F), and the active center (in Supporting Information Figure B) was identified by YASARA.…”
Section: Methodsmentioning
confidence: 99%
“…Solutions of samples were prepared by the reported method. 24 A susceptible population of M. separata, P. xylostella, S. f rugiperda, and Ostrinia f urnacalis has been reared in the department of bioassay, Nankai University, since 2006, 2010, 2019, and 2010, respectively. The 10 mg•mL −1 mother solution of the test compound was prepared by dissolving 10 mg of a sample in 1 mL of DMF.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations